Analisis Infrastruktur Teknologi Informasi pada PT RedEx Menggunakan Metode SWOT dan Mcfarlan Strategic Grid - Fatih Darmawan, Muhammad; Pahlevi, Febriansyah Reza; Fachmie, Azka Nur; Mahardika, Anggoro; Setiawan, Ito (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This study aims to analyze the information technology (IT) infrastructure of PT RedEx using SWOT and McFarlan Strategic Grid methods to evaluate internal and external factors affecting IT performance and its strategic positioning. The SWOT analysis identifies strengths, weaknesses, opportunities, and threats, while the McFarlan Grid maps IT systems into four quadrants: Strategic, High Potential, Key Operational, and Support. Data were collected through observation, interviews, and documentation. The results show that PT RedEx’s IT infrastructure supports operational activities but lacks real-time integration across branches. Based on the McFarlan analysis, most systems are in the Key Operational and Support quadrants, indicating a focus on daily operations rather than strategic innovation. Recommendations include system integration through cloud computing, digital transformation, and IT human resource development. The study provides insights into strategic IT planning for logistics companies in the digital era.